STRATEGI PENINGKATAN KUALITAS PUPUK KOMPOS MELALUI SERTIFIKASI STANDAR PUPUK PADA KSM SRIMENANTI JAYA SUNGAILIAT - Fabiani, Verry Andre (Fakultas Sains dan Teknik, Universitas Bangka Belitung, 2025)
In managing household waste, KSM Srimenanti Jaya has played an active role in supporting the efforts of both the community and the government. Their main services in Kelurahan Srimenanti include waste collection, provision of plant seedlings, and processing of domestic waste. However, until now, no laboratory testing has been conducted on the compost fertilizer they produce, so the quality of the product remains uncertain. Therefore, this community service program is aimed at improving the quality of compost through fertilizer standard certification for KSM Srimenanti Jaya. Based on laboratory test results, most of the compost quality parameters have met the requirements of SNI 19-7030-2004 and are deemed marketable. Nevertheless, some aspects such as pH level, presence of foreign materials, and particle size still need to be optimized. The program also includes outreach on strategies to enhance compost quality, distribution of pocket guidebooks, and the provision of large waste shredding machines. At the conclusion of the activities, an evaluation was conducted which showed that all KSM managers felt greatly assisted and understood the material presented in the program.